Quantitative analysis of drug–drug interactions among active components of Xuebijing in inhibiting LPS-induced TLR4 signaling and NO production - Tianshu Zhang; Hongyuan Li; Cong Lin; Xiaohui Wang (Scientific Reports)
Abstract Despite the long history of Traditional Chinese Medicine (TCM) in disease treatment, the underlying “Jun–Chen–Zuo–Shi” principle remains largely unexplored. To address this gap, it is essential to elucidate the interactions between active substances in TCM through quantitative molecular and cellular pharmacology. The Chou–Talalay method is particularly effective for investigating drug combinations, making it highly relevant for TCM formulas. This study employed the Chou–Talalay method to explore the drug–drug interactions in Xuebijing (XBJ), a TCM formula used for treating sepsis. The aim was to elucidate the “Jun–Chen–Zuo–Shi” principle by investigating the interactions of the main active substances in XBJ: danshensu and salvianolic acid B (from Radix Salviae Miltiorrhizae), senkyunolide A (from Rhizoma Chuanxiong), ligustilide (from Radix Angelicae Sinensis), safflower yellow and hydroxysafflor yellow A (from Flos Carthami), and paeoniflorin (from Radix Paeoniae Rubra). We quantitatively analyzed their TLR4 antagonistic activities and used the combination index (CI) to quantify their interactions, revealing synergism (CI < 1), additive effects (CI = 1), and antagonism (CI > 1). The results show these agents inhibit nitric oxide (NO) production, with some combinations demonstrating synergistic effects at certain concentrations, while others present antagonistic effects. Understanding these interactions provides a scientific foundation for optimizing TCM formulations, enhancing quality control, efficacy, and safety.